2016
DOI: 10.1039/c5cp06153a
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent strain and surface energies of gold nanoclusters

Abstract: Gold nanocluster properties exhibit unique size-dependence. In this contribution, we employ reactive molecular dynamics simulations to calculate the size- and temperature-dependent surface energies, strain energies and atomic displacements for icosahedral, cuboctahedral, truncated octahedral and decahedral Au-nanoclusters. The calculations demonstrate that the surface energy decreases with increasing cluster size at 0 K but increases with size at higher temperatures. The calculated melting curves as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 83 publications
2
62
0
Order By: Relevance
“…Nanoparticles may even exhibit a quasi-liquid or glassy structure, states having no equivalents in the bulk [14]. Recent calculations of the surface energy of gold as function of the particle size by Ali et al [51] have predicted an increase of the surface energy with decreasing particle size. However, these authors used the coordinates of the surface atoms to calculate the surface of the particle.…”
Section: Reviewmentioning
confidence: 99%
“…Nanoparticles may even exhibit a quasi-liquid or glassy structure, states having no equivalents in the bulk [14]. Recent calculations of the surface energy of gold as function of the particle size by Ali et al [51] have predicted an increase of the surface energy with decreasing particle size. However, these authors used the coordinates of the surface atoms to calculate the surface of the particle.…”
Section: Reviewmentioning
confidence: 99%
“…These figures have in common the leftmost curve, which is taken as a reference. It corresponds to uncharged NPs with the density of bulk Au V M = 0.01695 nm 3 , 5,7,41 the interfacial free energy γ ∞ = 0.980 J/m 2 as determined from recent MD simulations of Au NPs 45 (equivalent to γ n A n ≈ an 2/3 with a = 1.8765 eV, see Supporting Information), the dodecanethiol binding area A L = 0.1764 nm 2 as determined from experimental data 5,7,10 (see Supporting Information), a binding energy per ligand E n = 1.60 eV estimated from experimental observations (see Supporting Information), and a temperature of 120°C commonly used for DR with boiling solvent or silicon oil baths. 22,41 In other words, the reference curve includes no fitting parameter but only values estimated from recent publications.…”
Section: ■ Theorymentioning
confidence: 99%
“…Recently, most of the studies concern under-coordinated atoms [1][2][3][4][5][6][7], in particular those located at the edges and corners of nanoparticles, whose atomic scales is approximately N ¼ 4pK 3 =3 when the diameter K of the particles is in the range from 10 to 1 nm [8][9][10][11][12][13][14]. Indeed, experimental studies have reported an increase in chemical reaction rates with the relative number of these under-coordinated atomic sites [15][16][17].…”
Section: Introductionmentioning
confidence: 96%